HIV Encephalopathy in Perinatally Acquired Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The incidence and clinical progression of HIV encephalopathy among 128 HIV-perinatally infected children were studied at multiple US centers by the Women and Infants Transmission Study Group.